INNOVATIVE DEVELOPMENT OF SMALL AND MEDIUM-SIZED ENTERPRISES IN BULGARIA - Filipova, Milena; Yuleva-Chuchulayna, Radostina (Revista Inclusiones, 2021)
Over the past few years, faced with new dynamic bisence models and increasing competition in the market, many small and medium-sized enterprises are currently facing the need for a comprehensive review of their innovation activities. Innovation must be implemented from the core of the organization and to the smallest part of the production. By increasing the innovation in the production of it’s products, as well as implementing them in the production processes, small businesses will continue to develop even in the face of pandemics, crises, etc. The past year has shown most managers of small and medium-sized enterprises to monitor trends and developments in technology, digitization and continuous innovation in the market. In the context of pandemy or crisis situations, the need for the implementation of innovative practices and activities is evident in order to achieve greater flexibility and to maintain the competitive level. The main objective of this development is to systematize the definitions of the term "innovation" offered by various economists and to analyze the innovation development of small and medium-sized enterprises in the Republic of Bulgaria. The main research methods used in the development are contingent analysis, method of analysis and synthesis, intuitive and systematic approach, survey.